2018
DOI: 10.1007/s00204-018-2330-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between metabolism and structural elements of the alicyclic fentanyl analogs cyclopropyl fentanyl, cyclobutyl fentanyl, cyclopentyl fentanyl, cyclohexyl fentanyl and 2,2,3,3-tetramethylcyclopropyl fentanyl studied by human hepatocytes and LC-QTOF-MS

Abstract: Recently, a number of fentanyl analogs have been implicated in overdose deaths in Europe and in the US. So far, little is known of the molecular behavior of the structurally related subgroup; the alicyclic fentanyls. In this study, reference standards of cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and 2,2,3,3-tetramethylcyclopropyl fentanyl (TMCPF) at a final concentration of 5 µM were incubated with cryopreserved human hepatocytes (1 × 106 cells/mL) for 0, 1, 3 and 5 h. The metabolites formed were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 14 publications
8
45
0
Order By: Relevance
“…In a study reported by Åstrand et al, seven metabolites of CycP‐F were identified in in vitro incubations with cryopreserved human hepatocytes . Four of these metabolites were comparable to those reported here, with the major metabolite in both studies represented by the N ‐dealkylated metabolite.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…In a study reported by Åstrand et al, seven metabolites of CycP‐F were identified in in vitro incubations with cryopreserved human hepatocytes . Four of these metabolites were comparable to those reported here, with the major metabolite in both studies represented by the N ‐dealkylated metabolite.…”
Section: Resultssupporting
confidence: 86%
“…Since carrying out this work, a study investigating the correlations between metabolism and structural elements of alicyclic fentanyl analogues, including CycP-F, has been reported. 28 Seven metabolites of CycP-F were identified utilising cryopreserved human hepatocytes in vitro, with good correlation to the metabolites observed in this study.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations